Serpentine square wave microchannel fabrication with WEDM and soft lithography. (2021) - Mondal, Bappa; Pati, Sukumar; Patowari, Promod Kumar
Abstract: The use of microfluidic devices or systems is not limited to any particular department or sector. Presently, from the biomedical to cosmetic, environmental protection to engineering, the application of these devices is increasing enormously. The study on fabrication of such devices become one of the most developing fields of investigation in the current time. Microchannel fabrication via conventional so-called traditional fabrication techniques is a challenging task. Various researchers are developing different types of materials and techniques to fabricate microchannel for different kinds. Some of the materials are polymers, ceramics, and metals. In this article, an interesting process for the manufacturing of serpentine square wave microchannel with polydimethylsiloxane (PDMS) has been offered and explored. The complete process of fabrication of the microchannel has been discussed. It includes major two steps: serpentine square wave mold preparation and serpentine square wave microchannel fabrication. Primarily, the mold of the microchannel of serpentine square wave type with proper dimensions has been produced with the support of wire electric discharge machining and then using these molds, serpentine square wave microchannel of PDMS has been prepared by the soft lithography technique. The proposed process is helpful to manufacture microchannel as per the designed dimensions. From this study, researchers will be benefited by obtaining the guideline related to the serpentine square wave type microchannel fabrication with a cost-effective way.